Developing Best Practice in the Education of Cooperative Members - ., Sutrisno; Prameka, A S; Wardani, S I; Wahyuni, F (KnE Social Sciences, 2018)
The statement that a co-ops’ member is the most important asset [22] assumes that members of the cooperative have a central position in a cooperative. The central member position is due to the cooperative being an organization of, by, and for members. Furthermore, the presence of a central position is due to members having a function as owners and users of cooperative service. Member education, as one of the cooperative principles, is necessary because the members’ knowledge of the cooperative will support the role or central position of the members. Efforts to implement member education, among others, are implemented by means of best practice development. Best practice (dictionary.com) is a procedure or set of procedures that is preferred or considered as a standard within an organization, industry, etc. Best practice development is based on organizational management experience. This research was conducted on Multipurpose Cooperative Makmur Sejati Malang. Analysis of information from key informants is done by triangulation analysis. The findings of the research indicate that the analysis of best practices is in line with the stages of development of cooperative organizations as part of member education. Best practice, in establishing Rukun Ibu for example, gives awareness to members to avoid lending activities. In addition, best practice at development stage is emphasized on member education. The fact that the fulfillment of obligations is executed by the 12th, as well as the loan service starting on the 13th of each month, instills an understanding of the need to balance the fulfillment of obligations and the utilization of rights as members of the cooperative. Keywords: member education, best practice